The Sufficiency of the “Contactless Cards” Security Features in Preventing Fraud-A Malaysian Study - Banon Hosany, Mansourah; A. Rubasundram, Geetha (International Journal of Psychosocial Rehabilitation, 2020)
Contactless Cards are a revolutionary innovation in transaction payments. Little is known; however, about what shapes end users’ willingness and perception to use this method. The objective of this study is to compare the end-users and banks perception on the sufficiency of contactless cards. This research will use Fraud Diamond Theory, General Deterrence Theory and Technology Acceptance Model (TAM) to meet the objective of this study. This research aims to provide a more in-depth analysis; hence a mixed method has been used. The quantitative data was collected from 192 users via questionnaires in Malaysia to be able to evaluate the end user perspective of contactless cards. The results were then analyzed via the Statistical Package of the Social Sciences (SPSS). This were then used to gauge the perspective of banks using interviews to analyze key security mechanism for the most popular type of fraud including the relay attacks, electronic pickpocketing, theft and cloning through devices readily available on dark web. The findings of this research suggested that almost 80% of end users of contactless cards were unaware of the types of risks and security features of contactless cards. The interviews reflected that relay attacks are the most prominent risk and that the security measures in place were insufficient. Henceforth, this research recommends that banks need to have more effective awareness programs to educate the users of contactless cards of the risks and security features.